Article RETRACTED due to manipulation by the authors Effectiveness of m-gym media development in learning rhythmic gymnastics for students and lecturers in Indonesia - Eva Faridah; Indra Kasih; Sinung Nugroho; Esi Emilia; M. Irfan; Ridha Mustaqim; Samsuddin Siregar; Nurman Hasibuan; Mikkey Anggara Suganda; Didi Suryadi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to assess the effectiveness of M-Gym media in enhancing the learning experience of rhythmic gymnastics for students and lecturers in Indonesia. The development of M-Gym media integrates interactive digital tools and structured instructional content to support the pedagogical process in rhythmic gymnastics education. The research employed a mixed-method approach, combining quantitative assessments and qualitative feedback to evaluate the impact of M-Gym on learning outcomes. Quantitative data were collected through pretest and posttest evaluations to measure the improvement in students' performance and understanding of rhythmic gymnastics. Qualitative data were obtained from interviews and focus group discussions with students and lecturers, providing insights into their experiences and perceptions of using M-Gym in the learning process. The results showed a significance of (p=0.000 <0.05), hence there was a significant improvement in students' rhythmic gymnastics skills and knowledge, evidenced by higher posttest scores compared to pretest scores. In addition, feedback from lecturers and students highlighted the usability, accessibility, and motivational aspects of M-Gym, which contributed to a more engaging and effective learning environment. In conclusion, the M-Gym media development has proven to be an effective tool in enhancing the learning and teaching of rhythmic gymnastics, offering valuable support to both students and lecturers. This study recommends the wider adoption of M-Gym media in rhythmic gymnastics education across Indonesia to further improve educational outcomes and foster a more interactive learning experience.